2019
DOI: 10.1002/app.48786
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropy of poly(lactic acid)/carbon fiber composites prepared by fused deposition modeling

Abstract: It is well known that 3D printed parts prepared by fused deposition modeling (FDM) exhibit large anisotropy of mechanical properties. In this article, poly(lactic acid; PLA)/carbon fiber (CF) composites with different built orientations (X, Y, Z) were prepared by FDM. The effects of printing temperature, speed, orientations, and layer thickness on the mechanical properties of the composites were systematically investigated. The mechanical properties of PLA/CF composites show more significant anisotropy. The or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(28 citation statements)
references
References 19 publications
1
26
0
Order By: Relevance
“…This leads to lower tensile strength in the "upright" direction of the short fibre reinforced sample compared to the "up-right" orientation of neat polymers [47][48][49]. The weakness of "up-right" orientation of chopped CF/PLA was compared to the "flat" by Ding et al [50]. The tensile strength of the "flat" and "up-right" orientation in the article is approximately 52 MPa and 35 MPa, respectively.…”
Section: Building Orientationmentioning
confidence: 95%
“…This leads to lower tensile strength in the "upright" direction of the short fibre reinforced sample compared to the "up-right" orientation of neat polymers [47][48][49]. The weakness of "up-right" orientation of chopped CF/PLA was compared to the "flat" by Ding et al [50]. The tensile strength of the "flat" and "up-right" orientation in the article is approximately 52 MPa and 35 MPa, respectively.…”
Section: Building Orientationmentioning
confidence: 95%
“…To identify the effect of printing orientation, layer thickness and the printing temperature, Ding et al [ 152 ] carried out an experiment using a CF/PLA composite printed using the FDM process. The orientation of the specimens is present in Figure 7 b for better clarification.…”
Section: Fibre-reinforced Composite Printingmentioning
confidence: 99%
“… ( a ) Short CF immersed in Nylon matrix (onyx filament) [ 148 ]. ( b ) The orientation of the printed tensile specimens [ 152 ]. …”
Section: Figurementioning
confidence: 99%
“…The poor filament adhesion would increase the anisotropy of the printed part by lowering the mechanical properties in the building direction. 21 Other phenomena might also influence the effect of temperature on mechanical properties, such as crystallinity 10,22 or matrix degradation, 23 and cause a more difficult understanding of this thermal behavior. Printing speed and temperature are thought to interact, since printing speed can modify the time between two adjacent depositions, which is the time allowed for a filament to weld before the temperature falls below the glass transition.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding extrusion temperature, Spoerk et al 20 reported a positive effect, since an increase in temperature decreases viscosity and promotes filament adhesion. The poor filament adhesion would increase the anisotropy of the printed part by lowering the mechanical properties in the building direction 21 . Other phenomena might also influence the effect of temperature on mechanical properties, such as crystallinity 10,22 or matrix degradation, 23 and cause a more difficult understanding of this thermal behavior.…”
Section: Introductionmentioning
confidence: 99%